Bahan Ajar Mendemonstrasikan Naskah Drama Berbasis Kreatif untuk Meningkatkan Hots (Higher Order Thinking Skills) Siswa Kelas XI SMA - Indah Rahmadani, Liesna Andriany, Rita dan Rika Kartika (Medan Resource Center, 2022)
This study aimed to develop teaching materials for modules and LKPD with Creative-Based Drama Script Learning Materials to increase the HOTS in class XI SMA. The respondents were some material experts and design experts as validators of module teaching materials and LKPD. The research method used 4-D Research and Development by Thiagarajan which consists of four stages, namely define, design, development, and desseminition. This study was limited to development stage due to the pandemic situation so it cannot be carried out for the dissemination stage (desseminition). The material experts response to the developed teaching materials and LKPD modules gave an average score with the overall material aspect as 88.66% or